Infusing the palliative into paramedicine: Inter-professional collaboration to improve the end of life care response of UK ambulance services. (4th March 2021) - Murphy-Jones, Georgina; Laverty, Diane; Stonehouse, Joanne
Abstract : Paramedics frequently encounter patients requiring palliative and end of life care. This is anticipated to increase with an ageing UK population, a strengthening preference for care and death to occur in the home, alongside pressurized community services. Nationally education is lacking and despite localized efforts of improvement, widespread change within ambulance services to advance the quality of care for this patient group has been slow to emerge. This paper describes two UK ambulance service improvement programmes that have sought to address this need. South Western Ambulance Service NHS Foundation Trust and London Ambulance Service NHS Trust collaborated with a nationally renowned charity, Macmillan Cancer Support, to create innovative programmes of change. Both services targeted data exploration, valued inter-professional learning and effectively engaged local stakeholders. Experience demonstrates the need for collaboration with specialist palliative care and dependence on community services to access support and alternatives to hospital conveyance. This paper considers the future for end of life care leadership in UK ambulance services and the development of specialist paramedic roles. While the future of an alliance of paramedicine and palliative care is yet to be fully realized, our work exhibits the significant progress made by UK ambulance services.